Improving IS performance in organisations : towards an IS capability - Peppard, J. W. (Cranfield University, 2001)
Today, most organisations are fundamentally dependent on their information systems (IS) and would quickly cease to function should the technology that underpins their business activities ever come to a halt. Yet, despite this situation, research continues to highlight that in many organisations senior executives are dis-satisfied with the value they perceive they are deriving from investments in IS and are concerned with the inability of their organisation to capitalise on opportunities provided by technology. The research reported in this exposition addresses this problem of linking IS expenditure with organisational performance. In particular, this exposition demonstrates how the cumulative output of the included research papers has contributed towards improving IS performance and consequently the contribution of IS to the competitiveness of an organisation, illustrating that the research papers represent a substantial, continuous and coherent body of work. The cumulative output of these papers emphasise that improving IS performance is a complex and multi-dimensional proposition. It is an enterprise-wide concern and, crucially not an assignment that can be delegated to the IS function. Moreover, it is largely a people issue governed by the organisational legacy regarding IS experiences. The experiences of the organisations studied is that it not an easy undertaken, but can take many years to effect. The exposition concludes that all organisations must develop an effective IS capability if they are to leverage value through IS. While this exposition provides insights as to the nature and content of this capability, it notes that further development of this concept is required.